2015
DOI: 10.1088/2040-8978/17/11/114001
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman scattering of molecules in metallic nanogaps

Abstract: Surface enhanced Raman scattering (SERS) is a highly sensitive vibrational spectroscopy that allows for structural determination of analytes with utmost resolution. SERS remarkable sensitivity and non-destructive nature has been quickly embraced by the scientific community having a great impact in a number of fields such as: analytical chemistry; surface science; biochemistry and medicine among others. Here we present a contemporary review of SERS with a focus on studies conducted in metallic nano-sized caviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Here, we report the site-selection of a 1,4-benzenedithiol (BDT) single-molecule junction by simultaneous surface-enhanced Raman spectroscopy (SERS) [24][25][26][27][28][29] and current-voltage (I-V) 30,31 measurements, at room temperature. The observed I-V response reveals the existence of three meta-stable states arising from different adsorption sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report the site-selection of a 1,4-benzenedithiol (BDT) single-molecule junction by simultaneous surface-enhanced Raman spectroscopy (SERS) [24][25][26][27][28][29] and current-voltage (I-V) 30,31 measurements, at room temperature. The observed I-V response reveals the existence of three meta-stable states arising from different adsorption sites.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first in situ study to the correlation between the optical and electronic properties in single-molecule junctions. The SERS signals gain intensity from two independent contributions: electromagnetic (EM) and chemical (CM) effects 25,26 . The EM effect, which is the major contributing factor, originates from local field enhancement accompanied by the excitation of localized surface plasmon resonances on metallic nanostructures.…”
mentioning
confidence: 99%
“…It can be observed that the strongest enhancements are located at the plasmonic hotspots or the corners and edges of the octapod AuNPs, and these can be attributed to the plasmonic nanoantenna effect. [47] The simulations also indicate that the plasmonic enhancement is higher for a bi-layer (2 x 2 array) than that for monolayer or single particle arrangement. This is because there are more gaps in between the octapod Au NPs in the case of bi-layer arrangement (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…[1][2][3][4] At the fundamental level, it is an inelastic scattering technique that generates photons with a slightly different energy from the input. Such differences usually correspond to transitions between vibrational levels, while the electronic states stay the same.…”
Section: Introductionmentioning
confidence: 99%